The Knowledge Transfer of Female Micro Enterprises through Community-Services University Training Programs - Nurul Asiah; Wahyudi David; Tuti Widiastuti (Universitas Mathla'ul Anwar Banten, 2020)
This study is aiming to observe the role of community-services university training program to the participants knowledge on doing a micro enterprises and how effective the program to enhance the participant knowledge. The female micro enterprise group (18 persons) in South Jakarta was observed throughout the 5 months coaching. This study is applying the quantitative data collection based on the questionnaire and distributed prior and after the training programs. The finding of this study was the motivation of the most participant was household financial factors followed by hobby, skill of the participant as well as social factors. Most of the participant has been exposed by information through internet and they are most likely learns from internet. Training is the second sources for them for getting information. Financial investment and information of investment was the main obstacle for them to enhance their business beside managerial issues. This study found that training effectively delivers cognitive knowledge to the participant. This study concludes that training program may enhance the knowledge but further training is needed to enhance their attitude in doing business.